2019
DOI: 10.20961/carakatani.v34i2.29344
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change-Induced Agricultural Drought over Moist-Cool and Moist-Warm Climatic Zones: A Case Study in Ale and Adami-Tulu Woredas, in Oromia National Regional State, Ethiopia

Abstract: <span>Frequency and intensity of drought have troubled sustainable agriculture and worsened food insecurity of Ethiopians. This study aimed to investigate climate change-induced agricultural drought over the moist-cool and moist-warm climatic zones, using historical precipitation and temperature data recorded in the crop growing months for 35 years. The changes of temperatures and precipitation were analyzed using Mann Kendall trend test. Agricultural drought indices were analyzed using R-model by withdr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…Spring and summer minimum temperature of midland of east Wollega zone were significntly increasing trend at P<0.01.While its annual temperature was notably increased at P< 0.05 (Table 2). It is line with current study, Benti and Chimdi [24] reported significant increasing trends of summer and annual minimum temperature at western parts Ethiopia too. Minimum temperature of spring and summer of east Wollega zone lowlands were showed that significantly increasing trend at P <0.01 while its annual minimum temperature was especially increased at P < 0.05 (Table 2).…”
Section: Minimum Temperaturessupporting
confidence: 92%
See 2 more Smart Citations
“…Spring and summer minimum temperature of midland of east Wollega zone were significntly increasing trend at P<0.01.While its annual temperature was notably increased at P< 0.05 (Table 2). It is line with current study, Benti and Chimdi [24] reported significant increasing trends of summer and annual minimum temperature at western parts Ethiopia too. Minimum temperature of spring and summer of east Wollega zone lowlands were showed that significantly increasing trend at P <0.01 while its annual minimum temperature was especially increased at P < 0.05 (Table 2).…”
Section: Minimum Temperaturessupporting
confidence: 92%
“…Therefore, all selected crops were significantly correlated to drought indices (p<0.001) (Figure 6). This finding is compatible to the information generated by [24,33,34] in which maize crop yield was highlighted as the least affected by climate change at 21 st century and wheat was most vulnerable and also studied by Pant [26] stated that yield of maize was increased from1990 to 2010 in Ethiopia and Nepal.…”
Section: Impacts Of Agricultural Drought On Selected Crop Yields At W...supporting
confidence: 91%
See 1 more Smart Citation
“…Climate change-induced disasters can significantly affect ecosystems and various economic sectors, with agriculture and food security most notably vulnerable. Sudden and unforeseen climate-related crises can devastate livestock and crop yields, putting local food reserves at risk [22]. One of the efforts that can be made to reduce the negative impact of drought and the potential for lack is by adding organic material, which is applied as mulch.…”
Section: Land Management Suggestionmentioning
confidence: 99%
“…The availability of water even though in small quantities must be considered and its continuity maintained (Benti & Achalu Chimdi, 2019), so that an irrigation system needs to be carried out, and one of the appropriate irrigation systems to use is subsurface irrigation (Sadewa et al, 2016). Sub-irrigation system is one way of providing irrigation water that can be applied profitably (Yuswari, 2016), because the subirrigation system utilizes the power of capillaries (Septiana, 2014;Rinasari et al, 2016) to absorb water from underground to the root zone.…”
Section: Introductionmentioning
confidence: 99%